Forecasting Analysis of New Student Candidate Admissions Using the Simple Linear Regression Method - Sardo Pardingotan Sipayung; Zakarias Situmorang; Zekson Matondang; Masdiana Sagala (SEAN Institute, 2023)
The development of science and technology facilitates various aspects of life, including forecasting. Forecasting student enrollment in private universities can maximize the use of resources for services, facilities, infrastructure, and improving human resources. The regression method is used to measure the effect of promotional costs on increasing student enrollment in the future. This forecasting will be valid if an accurate model is used. The results showed the level of accuracy using the MAPE (Mean Absolute Percentage Error) model of 2.229%. However, the level of accuracy can vary each due to differences in data.